Finding the Relationship between Agriculture and Carbon Emissions in Pakistan: An Empirical Investigation - Muhammad Iatzaz Ul Hassan; Mengyun Wu; Yasir Rasool; Charles Mawuena Gates (PT Mattawang Mediatama Solution, 2024)
Pakistan’s economy depends on the agriculture sector which contributes approximately 25 percent to GDP and 45 percent to total employment. This research work inspects the link between agriculture value-added and carbon emit in Pakistan and other potential indicators for instance gross domestic per capita, Foreign direct investment, total population and resources energy. We retrieved data from the world indicators CD room spanning1988 to 2020 for this study and adopted auto regressive distributive log (ARDL) technique and Stata 18 version were used. The long run results of the study revealed that agricultural value-added, foreign direct investment, non-renewable energy utilization, population and Gross domestic per capita increased environmental deterioration. While consumption of renewable energy upsurge environment sustainability in the region. The outcomes also signpost the presence of bi-directional causality between the given indictors. The outcomes also signpost the presence of bi-directional causality between the given indictors. This study is only limited to only the Pakistan with specific indicators. Based on the empirical evidence, the study support to the agriculture sector through sustainable practices and green technological advancements to the economic growth and renewable resources to promote environmental sustainability in Pakistan.